The Food Safety Modernization Act (FSMA) Preventive Controls for Animal Food - Jason M. Scheffler; Chad Carr (EDIS)
The Food Safety Modernization Act (FSMA) was signed into law in January of 2011 and is considered the most sweeping reform of food safety regulations in 70 years. The human food regulations were composed first and, with significant input from industry, academia, and consumer groups as well as other agencies, were then modified to better suit animal food production. In Florida, these new regulations apply to facilities that manufacture, process, pack, or hold food or food ingredients for animals. These facilities may include pet food manufacturers, renderers, ethanol distillers, feed mills, distributors, and others. The primary goal of these regulations is to ensure safe food for the animals, people who handle the feed, and people who consume the final animal products. This 3-page fact sheet discusses requirements, facilities that will most likely be expected to be in compliance, deadlines, development of a food safety plan, and preventive controls for qualified individuals. Written by Jason M. Scheffler and Chad Carr, and published by the UF Department of Animal Sciences, December 2016.